Next step in the development of mesoprogestins: the preclinical profile of EC313 - Błaszczak-Świątkiewicz, K.; Krupa, A.; Mnich, E.; Elger, W.; Oettel, M.; Nair, H.; Wierzbicki, M.; Sieroszewski, P.; Shaked, Z. (Frontiers in Endocrinology, 2023)
The pharmacological target for progesterone, different progestins and the Selective Progesterone Receptor Modulators (SPRMs) is the nuclear progesterone receptor (PR). EC313 is a new member of a subgroup of SPRMs, so-called mesoprogestins, which combine especially PR-agonistic as well as PR-antagonistic activities in one molecule. The suitable in vivo-model for the differentiation of SPRM's from the subgroup of mesoprogestins is the estrogen-primed juvenile rabbit endometrium assay (so-called McPhail-Assay). Remarkably, in contrast to the well-known other SPRMs with no agonistic effects in this test, EC313 shows clear PR-agonistic partial effects that are higher than that of the well-known mesoprogestin Asoprisnil which already demonstrated remarkable clinical effectiveness for the treatment of uterine fibroids and endometriosis (1).The findings of presented here in guinea pig-studies were the impetus for further preclinical development of EC313. The EC313 treatment reveals PR-dominance at the genital tract and inhibits unopposed estrogenic effects. In very high doses (30.0 mg/animal/day s.c.) given twice on pregnancy, no premature labor was induced (in contrast to UPA, dosed at 10.0 and 30. mg/animal/day s.c.). The anti-ovulatory activity of EC313 exceeds that of Ulipristal acetate or Mifepristone. EC313 binds to the steroid receptors in vitro with a similar affinity as the natural ligand progesterone. No binding to the estradiol receptor was detected. A tissue selectivity of EC313 was demonstrated previously by reducing the growth and proliferation of uterine fibroids in animal model (lowest effective dosage 0.1 mg/kg/day s.c.). (2). As shown in this paper, the anti-fibroid activity of EC313 was confirmed with a dosage ten times lower (0.01 mg/kg/day s.c.). It was also shown, that EC313 reduces the growth of endometriotic lesions in human xenograft immune-deficient (NOD-SCID) mice model with a comparatively very low dosage range. For an explanation of these findings, the possibility is discussed that the mixed agonistic/antagonistic feature of EC313 is target-specific in terms of a superadditive synergism of a bifunctional principle. In conclusion, the specific pharmacodynamic profile of this compound opens the possibility for the development of a drug with a distinct pharmaco-endocrinological profile against uterine fibroids, endometriosis, and other PR-dependent gynecological diseases.